Analisis permintaan listrik rumah tangga perkotaan dan pedesaan di Provinsi Jambi (studi komparatif dan faktor-faktor yang mempengaruhinya) - Riani, Riani; Amril, Amril; Vyn Amzar, Yohannes (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
This study aims to determine and analyze the electricity demand of urban and rural households in Jambi Province (Comparative Study and Factors Affecting It). The dependent variable is household electricit demand, the independent variable includes: intensity of electricity use, income, number of electronic devices, house building area and number of family members. The research method is descriptive quantitative and comparative. Data were collected using questionnaires and analyzed using multiple linear regression through the SPSS IMB. The results showed from the comparative test that the electricity demand of urban and rural households in Jambi Province had differences. From the results of the t test (partial) it was found that the intensity of electricity use, income, the number of electronic devices and the area of the house building had a positive and significant effect on household electricity demand. Meanwhile, the number of family members has no positive and significant effect on household electricity demand. The results of the F test (simultaneously) show that the intensity of electricity use, income, number of electronic devices, building area of the house and number of family members affect household electricity demand.